Aspek ergonomi pada produk kursi dan meja siswa di Rehabilitasi Sosial Bina Netra (RSBN) Malang - Wahyu Waskito Putra (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
Chair and desk are kinds of school furniture that influence for posture. Usage of unergonomically desk and chair will cause musculoskeletal complaint in student. Based on preliminary research conduct to student of ABC elementary school grade 1 and grade 5 with checklist and Standard Nordict Questionnaire (SNQ). Result of checklist in student grade 1 in average stature 115,6 cm mismatch hight of desk and hight of chair with the student. Student grade 5 in average stature 133,7 cm mismacth hight of desk and hight of chair with the student. This cause student musculoskeletal complaints result with SNQ in neck, hand, foot, back, wait, elbow and knee. Unergonomic desk and chair cause bad posture. Mismatch of desk and chair minimalizeted by redesign desk and chair with antropometry of student according to Pahl and Beitz methods. Step of this methods are clarification of task, conseptual design, embodiment design dan detail design. Redesign of school desk and chair result adjustable hight of desk and hight of chair with hight of desk 41,4- 58,9 cm and hight of chair 30,2-40,6 cm. Width of desk 56,3 cm, width of chair 27,3 cm, lenght of chair 39,2 cm and height of backrest 43,5 cm.